Comparison of the Retro Screw and Standard Interference Screw for ACL Reconstruction - Wang, Robert Y.; Arciero, Robert A.; Obopilwe, Elifho; Mazzocca, Augustus D. (The Journal of Knee Surgery, 2012)
The objective of the study was to compare the load to failure between a retro screw (RS) and a standard interference screw (IS) for tibial-sided anterior cruciate ligament (ACL) fixation. We used 20 bovine tibia and extensor tendons for the study. A group of 10 specimens underwent IS fixation while the other 10 underwent RS fixation. Within each group, five specimens had graft suture in contact (interdigitating) with the screw threads. All specimens were tested on the MTS 858 Mini Bionix II (MTS Systems, Shakopee, MN). There was no statistically significant difference between the RS and IS with respect to peak load to failure. IS with suture interdigitation failed at an average of 520 N (range: 358 to 793 N), while the RS with suture interdigitation failed at 613 N (range: 438 to 1089 N). The IS without suture interdigitation failed at 654 N and the RS without suture interdigitation at 531 N. Specimens with a whipstitch in contact with the screw did not demonstrate higher pull out strength. The RS fixation strength appears to equal the IS. Graft suture contact with screw threads does not increase fixation strength. Based on this study, using a RS for tibial ACL soft tissue graft fixation is feasible and provides equal fixation strength compared with the standard IS.
Keywords: anterior cruciate ligament reconstruction; all-inside anterior cruciate ligament; retro screw; load to failure